Answer:
g= -5
Step-by-step explanation:
Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :
84-(4*(1-4*g))=0
84 - 4 • (1 - 4g) = 0
3.1 Pull out like factors :
16g + 80 = 16 • (g + 5)
16 • (g + 5) = 0
4.1 Solve : 16 = 0
This equation has no solution.
A a non-zero constant never equals zero.
4.2 Solve : g+5 = 0
Subtract 5 from both sides of the equation :
g = -5
I hope it helps you and if you want you can give me a brainly crown only if you want
Answer:7
Step-by-step explanation:
1/2 of j is the same as j ÷ 2
14 ÷ 2 = 7
Given that the roots of the equation x^2-6x+c=0 are 3+8i and 3-8i, the value of c can be obtained as follows;
taking x=3+8i and substituting it in our equation we get:
(3+8i)^2-6(3+8i)+c=0
-55+48i-18-48i+c=0
collecting the like terms we get:
-55-18+48i-48i+c=0
-73+c=0
c=73
the answer is c=73
Answer:
27
Step-by-step explanation:
Given the ratio 3 : 9
and 9 : ?
note that 3 × 3 = 9, thus 9 × 3 = 27
3 : 9 = 9 : 27
Answer:
Step-by-step explanation:
pyramid has a height of 5 inches and a volume of 60 cubic inches. Select all figures that could be the base for this pyramid.
A:
a square with side length 6 inches
B:
a 3 inch by 4 inch rectangle
C:
a 4 inch by 9 inch rectangle
D:
a circle with radius 4 inches
E:
a right triangle with one side 5 inches and the hypotenuse 13 inches
F:
a hexagon with an area of 36 square inches